Educational AR Mystery Puzzle Game for Children (International Journal of Innovative Computing, 2026)
AR (AR) has been on the rise in which it has been implemented in many fields. Children these days have low attention span when they have no electronic devices on them. To deal with this issue, the aim of this research is to design an educational AR mystery puzzle for children aged 4 to 6. Therefore, the objective of this research is to analyse the user engagement, problem solving skills and the learning outcome with the AR mystery puzzle with an interesting storyline and lastly, to evaluate the AR mystery puzzle design where it focuses on the usability. There are 2 levels provided in the prototype, for level 1 the users were required to choose one marker out of the two markers provided, and for level 2 the users were required to choose two markers out of the three markers provided to go through with the story.  Moreover, players can inspect the items before making the final decision and the leader board score is based on the time taken to finish the game. Waterfall methodology is used for this research since the workflow of the proposed game is an initial prototype to better understand its potential based on the objectives and scopes covered with a clear requirement. For the evaluation, usability tests are done as well as the functionality testing. The results showed that this proposed game design can inspire children for them to be exposed to an AR mystery puzzle game and be educated with essential life skills.
Keywords: Educational AR, Mystery Puzzle Game, Children